The Opportunities and Challenges of Jati Plus Perhutani - Corriyanti Corriyanti; Novinci Muharyani (Masyarakat Peneliti Kayu Indonesia, 2018)
The teak breeding program has long been conducted by Perum Perhutani and produced superior teak and was named Teak Plus of Perhutani - Jati Plus Perhutani (JPP). With good silviculture practices, JPP-teak of 9 year-old can produce no less than 100 m³/ha, with ± 60 cm of tree circumstance. The high demand for teak wood is an opportunity to develop JPP-teak with fast growing character. Research shows that the quality of JPP wood of 5 and 10 years of age can be classified into Strength Class III. Although the quality of JPP-teak is not equal as the teak gets older, it can be improved through several methods, such as densification, thermal modification, etc. Durability of fast growing JPP-teak can be enhanced by additional treatment with natural or chemical material preservation. Wood color modification can be done through heat treatment method. The color change of JPP-teak of 5 years of age that looked more brownies with variation in value of color change (ΔE*) of 1.04 to 48.53. Modification technology influenced the properties of teak wood and it is an opportunity of JPP to gain added value as a renewable forest resource product. With teak forest area covering 1.7 million hectares, Perum Perhutani has challenges in developing JPP-teak with more added value.